ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DAN LAYANAN DENGAN METODE IMPORTANCE PERFOMANCE ANALYSIS (STUDI KASUS MIE RAMPOK JIMBARAN) - Kurnia, Mei; Hartiati, Amna; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 1 (2018): Maret, 2018)
This study aims to know about the primary attributes at Mie Rampok Jimbaran to get the consumer satisfaction to know the grade of consumer satisfaction on product and service at Mie Rampok Jimbaran, and to choose which attributes should be the priority to be inproved by the company to achive the consumer satisfaction.  The study was conducted at Mie Rampok Jimbaran. The Sample is 98 respondents used judgement sampling method. The data collected by distributed questionnaires and directly to respondents. The study using importance performance analysis (IPA) method. The result showed that the highest grade of cunsomer satisfaction for product was variant of product with the compatibility level of 102,11 %. The lowest grade of customer satisfaction for product was product quality assurance with the compatibility level of 86,18 %. The highest grade of customer satisfaction for service was interior design is unique with the compatibility level 101,01 %. The lowest grade of  customer satisfaction for service was staff quick to treat consumer with the compatibility level of 88,97 %. The attributes that must have priority for product is product quality assurance, ingredients to used for product and product availability. The attributes that must have priority for service is the skilled staff, staff giving clear informations for consumer, staff quick to helping consumer and staff quick to treat consumer.        Keywords: consumer satisfaction, Importance Perfomance Analysis, product, service.